Development and validation of a Ni-based catalyst for carbon dioxide dry reforming of methane process coupled to solid oxide fuel cells. (21st June 2019) - Barelli, L.; Bidini, G.; Di Michele, A.; Gammaitoni, L.; Mattarelli, M.; Mondi, F.; Sisani, E.
Abstract: Recent studies propose dry reforming as a potential alternative to steam reforming. A number of advantages come mainly from the substitution of steam with CO2, representing a potential strategy for CO2 and waste heat reuse in both carbon-intensive industry (e.g. steel) and power generation applications (e.g. dry reforming coupling to solid oxide fuel cells). The objective of this study is the development, by means of an ultrasound assisted synthesis technique, of a novel 15%Ni -6%ZrO2 –3%CaO -Al2 O3 catalyst with high surface area and metal dispersion, to achieve high values of methane conversion and stable performance, obtained by significantly limiting carbon deposition at temperature in the range 700–750 °C. In this range, compatible with the dry reformer-SOFC thermal integration, conventional catalysts seriously suffer from coking tolerance issues. The catalyst exhibited very promising results with high methane conversion rates of 93% at 750 °C and 1.25 CO2 /CH4 ratio at the reactor inlet (dilution: in SiC 4:1 in volume), stable over 450 h of operation, with no significant changes in outlet gas composition and relevant modifications on material structure as revealed by SEM/EDX, XRD and Raman, analysis. Highlights: Ni–5%CaO–5%ZrO2 /Al2 O3 with high Ni dispertion thanks to US-assisted synthesis. High Methane conversion. Long time stability in the range at 750 °C. Low carbon coke deposition due to effects of CaO and ZrO2 . System integration between a dry reforming reactor and a SOFC system.